MANAJEMEN PEMELIHARAAN BABI BUNTING DI PETERNAKAN CV. ADHI FARM KARANG ANYAR, JAWA TENGAH - , DHAFIRA ITHMA ANNA, Drh. Dwi Priyowidodo, MP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Implementation of the Job Practice with subject âNon Ruminant's Animal Healthâ held in Pig Farm CV.ADHI FARM. Farms which managed by Mr. Alexander was located in Kebakkramat district, Karanganyar, Central Java. Non Ruminant's Job Practice in pig farm was held from 8th to 13th of April 2013. In accordance with the title for last assignment 'MAINTENANCE MANAGEMENT OF PREGNANT SOWS IN CV. ADHI FARM \", the author searched informations by field observation,got interview with officials and take part in the farm. During the working practice at the farm, the results are maintenance pregnant sows which in terms of the female parent selection, feeding, housing, and health care. Good maintenance is one of the key to be success on farm business which include maintenance pigs, feeding technique, control, and prevention of disease. Maintenance of pregnant sows in CV. Adhi Farm is quite good, in terms of holding the election, from sow selected by looking at the number of nipples, from the composition of the feed was fulfill , and health care done by precaution with supervision of biosecurity. housing of pregnant sows's individual cages and has separate with childbirth sow's cage . Exersice is not done on pregnant sows, but it is important to reduce the occurrence of obstructed labor.